160k views
4 votes
Solve for x in the equation x2-5x+1=3

User Tharkius
by
5.3k points

1 Answer

4 votes

x^(2) -5x+1=3

The first thing you should do to solve is set the equation equal to zero. Subtract 3 from each side:


x^(2) -5x+1=3 \\ \\ x^(2) -5x-2=0

The resulting equation doesn't seem to be factorable. To solve for x, use the quadratic formula:


x= (-b \pm √(b^2-4ac) )/(2a) \\ \\ x= (-(-5) \pm √((-5)^2-4(1 )(-2)) )/(2(1)) \\ \\ x= (5 \pm √(25-4(-2)) )/(2) \\ \\ x= (5 \pm √(25+8) )/(2) \\ \\ x= (5 \pm √(33) )/(2) \\ \\ x \approx (5 \pm 5.74)/(2) \\ \\ \\ \\ x \approx (5+5.74)/(2) \\ \\ x \approx (10.74)/(2) \\ \\ x \approx 5.37 \\ \\ \\ \\ x \approx (5-5.74)/(2) \\ \\ x \approx (-0.74)/(2) \\ \\ x \approx -0.37

To the nearest hundredths place, the solutions to the original equation are x = 5.37 and x = -0.37.
User LoranceChen
by
6.1k points